Delivering trauma training to multiple health-worker cadres in nine sub-Saharan African countries: lessons learnt from the COOL programme. (27th April 2015) - Peter, Noel Aaron; Pandit, Hermant; Le, Grace; Muguti, Godfrey; Lavy, Christopher
Abstract: Background: Africa has one of the highest road-traffic mortality rates in the world. Nurses and clinical officers play a pivotal part in trauma care as a result of substantial shortage of doctors. The COOL (COSECSA-Oxford-Orthopaedic-Link) programme has delivered primary trauma care (PTC) training in nine sub-Saharan African countries across a wide cadre of health-workers (540 doctors, 260 nurses, 119 clinical officers, and 111 medical students). This prospective study investigates the effect of 28 consecutive PTCs and the training challenges that exist between different cadres and health institutions. Methods: The course trains delegates in key trauma concepts: primary survey, airway management, chest injuries, major haemorrhage, and paediatric trauma. Candidates' knowledge of these concepts was assessed before and after the course with a validated 30 Single-Best-Answer multiple choice questionnaire. Assessment scores were analysed by cadre, urban (383 candidates) or rural institutions (647 candidates), and sex (657 men, 373 women). A concept was categorised as being poorly understood when half the candidates achieved less than 50% of the correct answers. Descriptive statistics and MANOVA analysis were used, with an alpha level set at 0·05. Findings: 1030 PTC providers were trained between Dec 5, 2012, and Dec 19, 2013. There was significant increase in multiple choice questionnaire (58% to 77%, p<0·05) and clinical confidence (68% to 90%, p<0·05) scores among delegates post course, with independent covariants of institution location and cadre significantly affecting post-course scores. Doctors achieved satisfactory scores on all key concepts (67% to 84%, p<0·05). Clinical officers (all concepts 53% to 76%, p<0·05) particularly struggled with paediatric trauma (94 candidates <50%, mean 24·23 [95% CI 19–30]). Nurses (all concepts 42% to 64%, p<0·05) had difficulty with chest injuries (203 pre-course to 153 post-course candidates <50%, mean 49% [95% CI 45–52]) and paediatric trauma (212 pre-course to 161 post-course candidates ≤50%, post course mean 46% [95% CI 43–53]). Medical students achieved satisfactory scores in all concepts (overall 53% to 74%, p<0·05). Health-workers based in urban hospitals (82%) outperformed those in rural hospitals (72%) (p=0·001) and sex had no significant effect on performance (p=0·07). Interpretation: Our study shows that PTC courses led to improvement in trauma management knowledge and clinical confidence among a wide cadre of health-workers. However, these are new concepts for many front-line health-workers, and regular refresher training will be required. There is also a difference in understanding of key trauma concepts among the different cadres. Future training in this region should address areas of weakness unique to each cadre, particularly paediatric trauma care. Funding: Health Partnership Scheme through the UK Department for International Development (DFID).